Developing sustainable single mother micro entrepreneurs business model in Terengganu - Mohd Huzir Mohamed
The purpose of this study is to develop a model that single mother micro entrepreneurs can use to succeed in the business of Terengganu. The design of this study is a case study of interviewees using qualitative approach. Respondents were obtained through government agency sources such as the Yayasan Pembangunan Keluarga Terengganu and the Terengganu Single Mothers Association. The authors also examine the challenges and problems faced by entrepreneurs as additional information to complete this study. There are three objectives of the study and the questions that are formulated to carry out this study and the results of this study are formulated as a conclusion. The government through the agencies involved has made various efforts to develop entrepreneurs in Malaysia, however, only a handful of entrepreneurs, especially among single mothers who are successful in the field of micro enterprises. Therefore, the authors wish to study the factors of their success and the results of the study will be built on a model for reference to single mother micro entrepreneurs in Terengganu. The author has also made several suggestions such as strengthening marketing strategies, brand awareness and also encouraging governments and the private sector to grow their business.